1981
DOI: 10.1159/000194421
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoidosis or Extrinsic Allergic Alveolitis?

Abstract: Of 46 patients with sarcoidosis, there was an exposure to type III allergens in 14 subjects. On closer examination of 2 patients diagnosed as having sarcoidosis there were distinct features suggesting farmer’s lung too. Inhalative challenge recording airway resistance, CO transfer factor and other clinical features confirmed farmer’s lung disease in these patients. Because there are sometimes poor clinical and uncertain histological differences, inhalative challenge is considered an important diagnostic proced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…Indeed, we found granulomas in spleen aspirates obtained by fme-needle biopsy in five out often patients with acute FL [14]. Granulomatotis changes in extrapulmonary organs have also been discovered by Konig et al [15], who reported a farmer with granulomas in liver tissue. A patient with pericarditis, which recurred on antigen re-exposure, has been reported by Reybet-Degat et al [16].…”
Section: Discussionsupporting
confidence: 52%
“…Indeed, we found granulomas in spleen aspirates obtained by fme-needle biopsy in five out often patients with acute FL [14]. Granulomatotis changes in extrapulmonary organs have also been discovered by Konig et al [15], who reported a farmer with granulomas in liver tissue. A patient with pericarditis, which recurred on antigen re-exposure, has been reported by Reybet-Degat et al [16].…”
Section: Discussionsupporting
confidence: 52%
“…The majority of affected individuals are nonatopic. A large group of antigens have been reported to cause granulomatous pneumonitis 2 and are generally of organic and inorganic matter. 3 Organic causes fall into two major groups, microbial spores and animal proteins.…”
Section: Discussionmentioning
confidence: 99%
“…1 Indeed, some have queried the possibility that sarcoidosis is an environmental disorder due to the inhalation of many antigens capable of sensitizing its host. 2,4 There may be a wide variety of substances in the environment that result in the formation of granuloma, such as beryllium, cobalt, titanium, and glass fibers. [5][6][7][8] Talc, a hydrated magnesium silicate, although usually associated with pleural fibrosis and calcified pleural plaque, can be found to cause nonnecrotizing granulomatous inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…These reactions after single challenge are reversible and therefore are an important diagnostic procedure to differentiate EAA from sarcoidosis. 93…”
Section: Lung Functionmentioning
confidence: 99%
“…This test should be performed by using a standardized protocol considering clinical symptoms and lung function parameters. 93,96 Other features distinguishing sarcoidosis from EAA include a negative Kveim-Siltzbach skin test and an increase of T-suppressor cells in BAL fluid. Erythema nodosum, bilateral hilar lymphadenopathy, uveitis, or abnormal calcium metabolism are not features of EAA (Table 10).…”
Section: Diagnosismentioning
confidence: 99%